Multivariable mobile robot motion controller - Okullo Oballa, Thomas S. (2009)
This thesis presents a new architecture for a cross-coupled motion controller for a mobile robot. It is applicable to mobile robots driven by DC motors with the differential drive configuration. This configuration is very flexible as it permits both linear motion and steering to be controlled by the same pair of wheels. This flexibilty leads to a tradeoff between maintaining the robot's orientation and its speed. This thesis postulates that this tradeoff can be reduced by employing a higher level of abstraction in controlling such robots. Thus more variables are introduced into the controller each an abstraction of the physical variable they are to control. Such controllers can then manipulate each variable while adjusting the other as necessary to maintain their status quo. The overall abstract control outputs can then be translated back to their low level equivalent in accordance with the associated model and applied to the actuators.